Naturally Occurring Norephedrine Oxazolidine Derivatives in Khat (Catha edulis) - Krizevski, Raz; Bar, Einat; Dudai, Nativ; Levy, Asaf; Lewinsohn, Efraim; Sitrit, Yaron; Ben-Shabat, Shimon (Planta Medica, 2012)
Khat (Catha edulis Forsk.) is a perennial shrub whose young leaves are chewed for their psychostimulating and anorectic properties. The main active principles of khat are believed to be the phenylpropylamino alkaloids, primarily (−)-cathinone [(S)-α-aminopropiophenone], (+)-cathine [(1S)(2S)-norpseudoephedrine], and (−)-norephedrine [(1R)(2S)-norephedrine]. GC-MS analyses of young leaf extracts indicated the presence of two oxazolidine derivatives, 2,4-dimethyl-5-phenyloxazolidine and 4-methyl-2-(trans-1-pentenyl)-5-phenyloxazolidine. To ascertain the chemical identity of these compounds, we synthesized the putative compounds by condensation of norephedrine and acetaldehyde or trans-2-hexenal, respectively. Spectroscopic analyses (GC-MS, NMR) of the structures of these synthetic compounds showed them to have identical retention indexes and mass spectra characteristic to 2,4-dimethyl-5-phenyloxazolidine and 4-methyl-2-(trans-1-pentenyl)-5-phenyloxazolidine. Marked differences in the ratios between each of these two norephedrine oxazolidine derivatives and total phenylpropylamino alkaloids were found among thirteen different khat accessions further indicating polymorphism in alkaloid ratios and content in C. edulis.
Keywords: Khat (Catha edulis; Celastraceae); norephedrine; phenylpropylamino alkaloids; phenyloxazolidine alkaloids; GC-MS